Exploring seniors perceptions of crime: a report of a social survey conducted in the city of Nedlands - Tarrant, Tessa (1991)
In this exploratory survey we investigated the perceptions of, and fear of crime in elderly persons. Interviews were conducted with eighteen elderly residents of the City of Nedlands, an age-heterogeneous community which enjoys a high socio-economic status. Due to the small number of people interviewed the survey is qualitative in character but reflects the perceptions of a particular segment of metropolitan elderly persons. It was shown that the participants consider that there is mere crime, of a more serious and threatening nature, in present times than there was fifty years age. There was no indication of fear of becoming victims of crime, however those who had been victims showed a greater concern. Most indicated that they felt secure in their present accommodation. None felt insecure enough to want to shift. Their lack of fear was demonstrated by the adoption of only basic security measures. Activities were not curtailed to any great degree, other than those that could also be attributed to age related activity decreases. Their concern regarding the increase in crime was net a personal concern but more a societal concern